Adverbial phraseological units in English, Russian and Karakalpak languages - Seytimbetova, Aykumar Pulatbaevna (The Lingua Spectrum, 2026)
The article is devoted to a comprehensive comparative analysis of adverbial phraseological units (PUs) in the English, Russian, and Karakalpak languages. The relevance of the study is determined by the need for an in-depth exploration of the phraseological fund as a tool for shaping an aesthetically significant linguistic picture of the world. The paper examines the structural and semantic characteristics of phraseologisms that reflect centuries of cognitive experience and cultural values. The framework is based on A.V. Kunin’s classification, within which adverbial and adjectival PUs are defined as nominative units. Special attention is paid to the phenomenon of functional syncretism and adjectival-adverbial transposition, allowing a single unit to combine various syntactic roles. The comparative aspect, involving the Karakalpak language, helps identify both universal cognitive models and national-specific features in the perception of reality. The author provides examples of full and partial equivalents, as well as non-equivalent units, demonstrating differences in the metaphorical conceptualization of the mode of action. The findings contribute to the development of comparative phraseology and typological linguistics, offering new perspectives for studying the interaction of language, cognition, and culture in diverse linguistic systems.